Biblioteca escolar como espaço de letramento - Enjiu, Andrea Jully (2012)
Reading has been widely approached at the national level through public policies, programs and research aimed at, in general, to collaborate with the democratization of information and knowledge and, therefore, are committed to the promotion of literacy. Considering that reading activities developed in school institutions are fundamental in this process, highlighting those implemented in their libraries, it is evident the importance of analyzing the conceptions and approaches used in this space for the systematization of speech-language pathways in the context of education. Thus, this study aims to investigate how library work has been instituted by a group of teachers from the metropolitan region of Curitiba. The field research was carried out with 56 primary school teachers, from 1st to 5th year, from the municipal network of Piraquara (PR). As a data collection instrument, a questionnaire composed of 16 questions was used regarding the following aspects: profile of subjects from identification and academic training; educators' views regarding the school library and the practices developed in that space, as well as their view on infrastructure, collection and use of the site. Based on the answers provided, the results indicate that the library in the municipality is still a poor environment in the school context, given the significant number of schools that do not yet have it (54%) and the number of teachers who do not activities (37%). The academic background of the teacher has shown little impact in relation to theoretical / practical content regarding the library and its restricted view about the functions of the school library, denoting the condition of teacher's literacy, does not allow it to be considered an integral part of the school, something apart. Consequently the practices that can be developed in the library are not considered pedagogical practices capable of inserting the subject in the literate world, but as pedagogical support. In this way, the research evidences the school library as a place of literacy promotion, which should provide meaningful reading practices. Faced with this fact, such study evidences the school library as a place of action of the speech therapist within the educational context, through practices of collaborative positions that contribute both to the constitution of school libraries and promoting in partnership with all involved in the school context, continuous actions that privilege the social and educational function of the library and meaningful reading practices.